HIT Solar Cell Performance Enhancement with Luminescent Down Shifting Phenomenon - Lin, Albert; Huang, Chien-Yao; Parashar, Parag; Chou, Hao-Ming; Lin, Yi-Shiuan; Kao, Ming-Hsuan; Chen, Shih-Wei; Shen, Chang-Hong; Shieh, Jia-Min; Chen, Tzu-Yu; Lin, Chien-Chung; Yu, Peichen; et al. (My University, 2018)
Luminescent down-shifting (LDS) phenomenon has been employed to enhance the HIT solar cell efficiency. The efficiency and J(SC) are increased by 2.3% and 11.5% respectively. External quantum efficiency (EQE) data supports our claim.